Apuntes para introducir la interseccionalidad en la enseñanza del derecho constitucional - Fernández Meijide, Camila (2020)
The aim of this paper is at presenting a short summary of the theoretical development of the concept of intersectionality, and thinking about its application for teaching Constitutional Law. First, I described some of the theories and academic and activist traditions that inspired Kimberlé Crenshaw's work on intersectionality. Then, I analyzed the concept of intersectionality, and compared it to other ways of thinking about discrimination and inequality that are rooted in different oppression vectors. In the second part of the paper, I returned to some ways of conceptualizing intersectionality that I find useful for the practice and research of the Law; inspired in the works by Laura Clérico and Martín Aldao, I appraised intersectionality as an adequate tool and methodology to enforce Article 75 (23) of the Argentine Constitution